The Role Of Brand Attachment And Brand Trust On Customer Retention With Brand Loyalty As An Intervening Variable On Bank Bjb Kc Medan Customers Intervening On Bank Bjb Kc Medan Customers - Sayed Muhammad Hanif; Mesrab Mesrab (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effect of brand attachment and brand trust on customer retention with brand loyalty as an intervening variable on customers of Bank BJB Medan Branch Office. The method used is a quantitative approach with Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis techniques on 154 respondents. The results of the study indicate that brand attachment and brand trust have a positive and significant effect on brand loyalty and customer retention. In addition, brand loyalty is proven to be able to mediate the effect of brand attachment and brand trust on customer retention. These findings reinforce the importance of building emotional attachment and customer trust in increasing brand loyalty and customer retention in the conventional banking sector. This study provides theoretical and practical contributions in designing sustainable customer relationship-based marketing strategies.